Analisis Zonasi dan Kesesuaian Kebijakan Pemanfaatan Lahan pada Kawasan Bencana Longsor - Ridha, Rasyid; Susanti, Febrita; Yunanti, Sri Rahmi (Department Geography Education Faculty of Social Science - Universitas Negeri Jakarta, 2024)
Gunungsari is located in West Lombok, which has a physical condition that is prone to landslides. Based on previous research using paimin vulnerability analysis, there are 4 categories of landslide susceptibility, namely the fairly high category, the medium category, the mild category and the moderate category. This study aims to analyze in terms of spatial planning policies in West Lombok regarding the regulation of landslide-prone areas and land use. This study uses a qualitative descriptive method using primary and secondary data. Spatial planning is an effort to realize an orderly spatial arrangement by taking into account the state of the environment, by looking at the spatial planning policy and field conditions, it will get a picture of the suitability between zoning and policies that have been determined with the use of the land, from the results of the analysis with the criteria for the vulnerability of the area to landslide-prone areas and functions. the area in Gunungsari has 8 zones, of which zones 1 and 4 have the function of permanent protection forest utilization, while zone 2, zone 3, zone 5 and zone 6 have undeveloped cultivation utilization. For zone 7 and zone 8 with the use of developed cultivation, if viewed from the aspect of spatial planning policies that can be following with the results of the analysis, however, there is a need for a detailed plan to regulate the use of existing space in Gunungsari, especially in areas prone to landslides.